(untitled) (Eurasian Research Bulletin, 2023)
The excise tax is one of the most important taxes in the economy of Uzbekistan and brings significant revenue to the budget. However, despite this, there are some problems in the process of its administration, such as lack of transparency of procedures, the presence of unjustified benefits and problems of interaction with other tax authorities. In this regard, the improvement of the excise tax system is an urgent task for the economic development of the country. To address these challenges Measures such as simplification of administration procedures, increased transparency, reduction of unjustified benefits, improvement of interaction between tax authorities and others are proposed. In addition, it is necessary to carry out more effective work to monitor the implementation of excise tax legislation